Observation of ultra-large Rabi splitting in the plasmon-exciton polaritons at room temperature - Zhang Min; Tian Yuan; Chen Xingzhou; Sun Zheng; Zhu Xiaolong; Wu Jian (Nanophotonics, 2023)
Modifying the light–matter interactions in the plasmonic structures and the two-dimensional (2D) materials not only advances the deeper understanding of the fundamental studies of many-body physics but also provides the opportunities for exploration of novel 2D plasmonic polaritonic devices. Here, we report the plasmon-exciton coupling in the hybrid system with a plasmonic metasurface which can confine the electric field in an extremely compact mode volume. Because of the 2D feature of the designed and fabricated Al plasmonic metasurface, the confined electronic field is distributed in the plane with the same orientation as that of the exciton dipole moment in the transition metal dichalcogenides monolayers. By finely tuning the geometric size of the plasmonic nanostructures, we can significantly modify the dispersion relation of the coupled plasmon and the exciton. Our system shows a strong coupling behavior with an achieved Rabi splitting up to ∼200 meV at room temperature, in ambient conditions. The effective tailoring of the plasmon-exciton coupling with the plasmonic metasurfaces provides the testing platform for studying the quantum electromagnetics at the subwavelength scale as well as exploring plasmonic polariton Bose–Einstein condensation at room temperature.